TopoIIα prevents telomere fragility and formation of ultra thin DNA bridges during mitosis through TRF1-dependent binding to telomeres - d’Alcontres, Martina Stagno (Landes Bioscience, 2014)
Telomeres are repetitive nucleoprotein structures at the ends of chromosomes. Like most genomic regions consisting of repetitive DNA, telomeres are fragile sites prone to replication fork stalling and generation of chromosomal instability. In particular, abrogation of the TRF1 telomere binding protein leads to stalled replication forks and aberrant telomere structures known as “multitelomeric signals”. Here, we report that TRF1 deficiency also leads to the formation of “ultra-fine bridges” (UFB) during mitosis, and to an increased time to complete mitosis mediated by the spindle assembly checkpoint proteins (SAC). We find that topoisomerase IIα (TopoIIα), an enzyme essential for resolution of DNA replication intermediates, binds telomeres in a TRF1-mediated manner. Indeed, similar to TRF1 abrogation, TopoIIα downregulation leads to telomere fragility and UFB, suggesting that these phenotypes are due to decreased TopoIIα at telomeres. We find that SAC proteins bind telomeres in vivo, and that this is disrupted upon TRF1 deletion. These findings suggest that TRF1 links TopoIIα and SAC proteins in a pathway that ensures correct telomere replication and mitotic segregation, unveiling how TRF1 protects from telomere fragility and mitotic defects.